Kompetensi Digital Guru-Guru Pesantren Al-Kautsar Melalui Pelatihan Teknologi Pendidikan - Sukmawati, Cici Emilia; Juwita, Ayu Ratna; Latifah, Nurul; Khairani, Nova Pustita (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2025)
The digital literacy skills of teachers in Islamic boarding schools are still low, especially in the use of technology to support learning activities and academic administration. One of the challenges faced is the lack of skills in using word processing software to systematically compile teaching materials and academic documents. This community service aims to improve the digital competence of Islamic boarding school teachers through training in the use of word processing software. The method used is a participatory approach with stages of planning, implementation of training based on direct practice, and evaluation through pre-tests and post-tests. This activity involves Islamic boarding school teachers as the main participants who receive intensive training in document creation and formatting, table management, and the use of automation features such as mass mailings and tables of contents. The results of the community service show an increase in participants' skills in operating word processing software, as indicated by an increase in post-test scores compared to the pre-test. In addition, this training also resulted in significant social changes, such as increased digital literacy of teachers, the emergence of individuals who act as mentors for colleagues, and the adoption of technology in academic administration. This program proves that a direct practice-based approach is effective in improving the digital skills of Islamic boarding school teachers. For the sustainability of the program, it is recommended that there be further training, a mentoring system between teachers, and technological infrastructure support so that the implementation of digital skills can take place optimally and sustainably.